Hubungan Perilaku Kesehatan Menggosok Gigi dengan Karies Gigi pada Anak Usia Sekolah di SDN Karangsari Cianjur Tahun 2022 - Rindiani Kurnia; Weslei Daeli; Yeni Kyoto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Dental caries is the most common disease found in the oral cavity together with periodontal disease, so it is a major problem for dental and oral health. This disease occurs due to demineralization of tooth surface tissue by organic acids derived from foods that contain sugar. Purpose: This study aims to determine the relationship between tooth brushing health behavior and dental caries in school-age children at SDN Karang Sari Cianjur in 2022. This research is a chi-square study with a cross sectional study design with a total sample of 40 respondents. Results: 27 people who suffer from caries and 13 people do not suffer from caries. After conducting the chi-square test, the value of the diet is 0.001 <0.05, which means that health behavior and dental caries have a significant relationship.